The Effects of Covid-19 Lockdowns on Income Distribution in South Africa: A Literature Review Perspective - NTOMBI W GAMEDE (African Journal of Governance and Development, 2022)
The discussion of COVID-19 and public health policies has gained importance since the emergence of the pandemic, but the effects that the pandemic has had on income distribution has not yet been given much academic attention. Income distribution is key for economic growth and human development, and promotes unity, solidarity and togetherness in society. It helps to understand poverty, and increases economic growth. However, the COVID-19 pandemic and lockdown measures used to contain and prevent the spread of the disease have had effect on households, unemployment, health and social protection. Lockdown regulations impacted on the income distribution as people could not work or travel without having permission from the authorities. The measures also restricted people regarding the manner in which they spent and distributed their income. Lockdowns led to the suspension of basic services and locked down activities such as reservations, local and international flights, and other support services. The paper found that the lockdown measures had tremendous effect on employment, production, and demand, resulting in a decline in the demand and supply of many industries, thus lowering income distribution. The paper also found that the pandemic lowered and deepened the existing inequality in income distribution and affected economic development in the country. To arrive at these assertions, the paper adopted a qualitative methodology design and explanatory approach.